"Opt-out" or pushed out?: Factors influencing married women professionals' decision in leaving the workforce. Issue 9 (4th November 2019) - Lim, Wee Ling; Mohd Rasdi, Roziah
Abstract : Purpose: The purpose of this study is to explore the challenges faced by married women professionals in the private sector and the factors affecting their decisions in leaving the workforce. Design/methodology/approach: A qualitative approach was used in this study. Data were obtained using a purposive sampling method in selecting ten married women professionals based on the inclusion criteria for this study. Semi-structured interviews were conducted and the whole interview sessions were audio recorded. Thematic analysis using the constant comparative method was used in interpreting the data. Findings: The findings of this study revealed that majority of the married women professionals leaving workforce are affected by "pushed out" factors such as workplace inflexibility, long working hours, high volume of work than "opt-out" factors, which focus on the biological and psychological "pulls" that lure women back into their traditional roles of motherhood. Most of the married women professionals interviewed had no intention to return to the workforce and had lost confidence to join back the workforce. Research limitations/implications: This study involved married women professionals in the private sector only. As a qualitative study, it limits to voice and views of these particular subjects only and could not be generalised to other group of women. Practical implications: The findings from this study shall enlighten all parties involved such as women professionals, HR managers and private sector organisations in strategies and plan of action towards minimising the talent drain of women professionals. Originality/value: This paper offers new insight into debating the opt-out or pushed out factors influencing married women professionals' decisions in leaving the workforce. It provides voice and views of women professionals who faced a predicament in making a decision about their career development.